Frades, artistas, filósofos: o Convento de Santa Maria Madalena e a atitude franciscana frente à natureza – ontem e hoje - Magalhães, Ana Cláudia Vasconcellos (2005)
The deal with nature permeated and supported all civilizations, in higher or lower degrees of intensity, either by mythical representations supported by it or by its capability of providing the species and the place with their basic needs of surviving. San Francisco, in a full Middle Ages, sets a new perspective into this relation, narrowing it, conceiving it in fraternally Christian and, taking a contemporary term, ecological basis. In this context, the Franciscan architecture was developed, which - based on theological and philosophical presuppositions established since San Francisco - intended to establish a communication channel with nature through permeable and available convent buildings to integrate with its natural compelling. This study intends to investigate and analyze in which means and how far this intension was reached and materialized at the old Convento de Santa Maria Madalena, a borough of Marechal Deodoro / AL. As a result of new religious and cultural dynamics, its just religious acting was overcame when some interventions were outlined from several uses performed at the old convent, which caused changes on its original appearance. The building, as a whole thing, suffered changes. All of them were significant, no doubt, regarding to its typology and environment. However, some of them go off at a tangent in terms of the relation between the building and the natural and compelling urban space, and constitute breaks and fragments in a dialog that used to happen between the convent and the landscape, the convent and the local folks. At present it performs a museum function, as a Museu de Arte Sacra do Estado de Alagoas has been settled in the building, which holds a valuable artistic and cultural collection. Considering this new function, it was also suitable to discuss the consequences of this relation with nature (established on its genesis as a convent building), to the collection preservation (primordial function of the museum building), when it is known that these relation results are absorbed by the property in an everyday routine, constituting a fundamental data for its preservation or destruction.